LITERASI KEUANGAN MELALUI GEMAR MENABUNG PADA ANAK SEJAK DINI DI SD NEGERI 1 DUWET KELURAHAN DUWET KECAMATAN BAKI KABUPATEN SUKOHARJO - Sarsono, Sarsono; Istiqomah, Istiqomah; Kustiyah, Eny; Prasetya, Sosiawan Aji; Rafli, Muhammad; Lestari, Dewi (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2023)
Financial Management is important for managing finances, one of which can be done by saving. Saving must be instilled from an early age. Because savings have an important role in the future. Saving is one way to manage money. The easiest way to save is at home because you can do it any time. SD Negeri 1 Duwet is one of the public elementary schools in Kelurahan Duwet, where the majority of parents work as entrepreneurs, civil servants, and laborers. The children of SDN 1 Duwet City are a little further behind than other public SDs where the parents' lack of interest in education can be seen from the lack of people with a bachelor's degree. Low education has an impact on a lack of understanding in financial management. Community service activities are carried out using the lecture method about the importance of saving, the practice of decorating piggy banks for places to save, giving rewards to children whose piggy banks are best decorated. As a result of this activity the children were very enthusiastic and gave a positive response by listening and competing to decorate their piggy banks, so that it is hoped that the mentality of children who are more thrifty and can spend the pocket money given by their parents wisely and diligently saves